Enhancing Productivity: Intervention Strategies for Employee Turnover Management in Hospitality and Tourism Industry - Miluwi , Joshua 0. (Gyan Management Journal, 2014)
The continual high turnover rate in the tourism and hospitality industry is the most problematic managerial topic. Using a sample of 304 travel agency employees, this research aims to identify differences in turnover antecedents between newcomers from graduate school or other industries and newcomers from the same industry. The results suggest several differences in both newcomer groups. Supervisor support is an antecedent for veterans, whereas personnel management, prospects and jobrelated factors are only significant for neophytes. External causes were revealed as the most significant antecedents in both groups, whereas co-worker support was not significant for turnover intention in either group.